The Influence of Service Quality on BPJS Health Patient Satisfaction in the Outpatient Unit at Mitra Siaga Hospital, Tegal - Dahlan, Muslih; Widjanarko, Bagoes; Jati, Sutopo Patria (JURNAL INFO KESEHATAN, 2023)
Good health services provide services that are effective, safe, and of high quality.  Efforts that have been made by the management of Tegal MS Hospital in maintaining and improving the quality of service, namely by holding training and simulation of excellent service, socializing BPJS Health related to a tiered referral system, equipping medical and non-medical equipment, repairing infrastructure, and carrying out standardization according to accreditation guideline assessments.  This research was conducted to determine the effect of service quality on BPJS Health patient satisfaction in the outpatient unit of Tegal MS Hospital. This type of research is observational research with a quantitative approach. The population in this study were BPJS Kesehatan patients in the outpatient unit of Tegal MS Hospital who met the inclusion criteria of this study. Based on calculations with the Slovin formula above, a research sample of 99.9 was obtained, and the results were rounded up to 100 respondents. Data analyzed use univariate analysis, bivariate analysis, and multivariate analysis. The infrastructure variable positively and significantly influences patient satisfaction with a p- value of 0.026 <0.05. Research results from Infrastructure variable, variable Personnel Quality, Clinical Care Process Variables, Administrative Procedure Variables, Variables Patient Safety Indicator, Hospital Image Variable, Social Responsibility Variable, Trust Variable to House Sick has a positive and significant effect on patient satisfaction variables with the results of p- values each variable < 0.05. To examine patient satisfaction, apart from using service quality as the dependent variable, future researchers are also expected to be able to add other dependent variables such as hospital cost factors, patient emotional factors, or family economic conditions and even other variables that might affect the level of patient satisfaction.